Newly Emerging Standards of Auditor Responsibility: A Reply. - Causey, Denzil Y. (The Accounting Review, 1977)
Abstract Presents a response by Denzil Y. Causey to a letter to the editor commenting on his article "Newly Emerging Standards of Auditor Responsibility," previously published in the January 1976 issue of "The Accounting Review."